Original paperC-reactive protein as a predictor of major adverse cardiac events (MACE) after percutaneous coronary intervention? - Markuszewski, Leszek; Rysz, Jacek; Makowski, Marcin; Dębska, Agnieszka; Pietruszyński, Robert (Archives of Medical Science, 2005)
Introduction: Interventional procedures, such as percutaneous coronary intervention (PCI) have significantly improved the prognosis in patients with acute coronary syndromes (ACS). Despite the introduction of new methods the problem of in-stent restenosis in coronary arteries is still being discussed. Therefore finding predictors of this process is crucial. Elevation of C-reactive protein (CRP) can be a useful predictor for restenosis and other major adverse cardiac events (MACE) after PCI. Material and methods: The studied group consisted of 33 patients (23 males and 10 females; mean age 62.9±8.9) admitted to our Department with myocardial infarction (MI) in whom MACE occurred during 6 months follow-up period. The control group consisted of 33 patients (21 men and 9 women; mean age 61.8±9.8) admitted to hospital for MI, in whom no MACE occurred during 6 months follow-up period. In all patients coronarography was performed and concentrations of CRP were measured, using high sensitivity diagnostic ELISA method (hsCRP). An incorrect level was determined as higher than 6 mg/dl. Patients have been observed during 6 months follow-up. History data were taken from everyone, including information about incidences of MACE or restenosis. Results: Both studied groups did not differ in parameters describing: sex, age and number of people. In patients with MACE, mean CRP concentration was significantly higher (median 4.8 mg/dl ±; 1.9-11.4) in comparison with the control group (median 2.2; 1.3-4.3); p<0.05. Conclusion: CRP concentration can be a predictor of MACE after successful PCI.